2008
DOI: 10.1002/dvdy.21440
|View full text |Cite
|
Sign up to set email alerts
|

Wnt6 expression in epidermis and epithelial tissues during Xenopus organogenesis

Abstract: Here, we report the localization within embryonic tissues of xWnt6 protein; together with the temporal and spatial expression of Xenopus laevis Wnt6 mRNA. Wnt6 expression in Xenopus embryos is low until later stages of neurulation, when it is predominantly found in the surface ectoderm. Wnt6 expression increases during early organogenesis in the epidermis overlaying several developing organs, including the eye, heart, and pronephros. At later stages of development, Wnt6 mRNA and protein generally localize in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…As expected Wnts were detected in additional regions (Figures 1 and 2) with some of them reported earlier [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30]: Wnt1 , Wnt2b , Wnt3a , Wnt8b , Wnt10a and Wnt10b are in the nervous system; Wnt5a , Wnt5b , Wnt7a , Wnt9a , Wnt11 , Wnt11b and Wnt16 are in the heart region; Wnt3a , Wnt7c , Wnt8a , Wnt8b , Wnt9a , Wnt9b and Wnt10b are in the epidermis; Wnt7a and Wnt7b are in the lateral plate mesoderm; Wnt11 and Wnt11b are in the somites; finally, Wnt3a and Wnt6 are in the ear.…”
Section: Resultssupporting
confidence: 85%
“…As expected Wnts were detected in additional regions (Figures 1 and 2) with some of them reported earlier [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30]: Wnt1 , Wnt2b , Wnt3a , Wnt8b , Wnt10a and Wnt10b are in the nervous system; Wnt5a , Wnt5b , Wnt7a , Wnt9a , Wnt11 , Wnt11b and Wnt16 are in the heart region; Wnt3a , Wnt7c , Wnt8a , Wnt8b , Wnt9a , Wnt9b and Wnt10b are in the epidermis; Wnt7a and Wnt7b are in the lateral plate mesoderm; Wnt11 and Wnt11b are in the somites; finally, Wnt3a and Wnt6 are in the ear.…”
Section: Resultssupporting
confidence: 85%
“…Instead, increased Wnt signaling in the pre-cardiac mesoderm prevents CM differentiation, which we hypothesize eventually leads to apoptotic death of the CPs via a p53/Caspase-3 independent mechanism. One possible explanation for this discrepancy is that in previous studies the CP and differentiation markers were assayed concurrently at later time points, not progressively over time points when the progenitor markers are first expressed (Afouda and Hoppler, 2009; Afouda et al, 2008; Foley et al, 2007; Foley and Mercola, 2005; Lavery et al, 2008a; Lavery et al, 2008b; Martin et al, 2010; Marvin et al, 2001; Naito et al, 2006; Tzahor and Lassar, 2001; Ueno et al, 2007). This leaves open the possibility that exploring additional time points could explain differences between this and previous studies.…”
Section: Discussionmentioning
confidence: 93%
“…In most present studies, Wnt6, a canonical Wnt signaling molecule whose expression remained strong in the epithelium, regulated the development of many tissues like heart muscle (25) and somite formation (26). During the development of the anterior part of the chicken eye, Wnt6 was expressed in the entire ocular surface epithelium, but the authors (27) also found Wnt6 in the iridial mesenchyme at the final phase of development.…”
Section: Discussionmentioning
confidence: 95%